URBANISATION AND THE CONCERNS FOR FOOD SECURITY IN MALAYSIA - Marzuki, Azizan; Jais, Ahmad Sahir (PLANNING MALAYSIA, 2020)
Urbanization is an effect of population growth. Increasing population contributed to the expanding of urban areas as cities try to accommodate more people within a minimal landscape. Urbanization takes up valuable land, sometimes productive agricultural land that feeds the population. The objectives of this paper are to investigate the connection between urban sprawl and its impact on agricultural productivity, and ultimately whether it affects food security in Malaysia. For this qualitative exploratory review exercise, a Systematic Literature Review (SLR) of secondary data was employed as the base for this study. Data mining techniques were used to gather relevant literature that included archival data, academic writings, and publications. The data are then dissected, analysed, and clustered using Atlas ti 8 software, focusing on thematic analysis. Urbanisation did affect the self-sufficiency level (SSL) of Malaysian food security, especially on landintensive food products such as vegetables and livestock. Recent government initiatives such as urban farming, land use policies were promoted to reduce the differences in food imports, ensuring Malaysian food security to be at an acceptable level. Significant development of this population dense proximity has created urban sprawl beyond the city limits, taking up valuable land space. Land-use conversion from agricultural land in Malaysia has been studied regarding its adverse effects on agricultural production. Urbanization therefore does affect food security through the land conversion of agricultural lands.